2016
DOI: 10.1038/srep39180
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between handedness and joint involvement in rheumatoid arthritis

Abstract: Rheumatoid arthritis (RA) is characterized by autoimmune chronic joint inflammation, which is worsened by mechanical stress. It is still inconclusive whether joints on the right side or the dominant side get more damaged in RA since the limited number of patients analyzed in the previous study had made it difficult to separately analyze right-handed and left-handed patients. Here, we enrolled 334 RA patients, the biggest number of patients in studies to address this issue and separately analyzed right-handed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…A total of 563 RA patients were enrolled from the KURAMA (Kyoto University Rheumatoid Arthritis Management Alliance) cohort and followed up prospectively. The KURAMA cohort was established in 2011 at the Center for Rheumatic Diseases in Kyoto University Hospital for tight/proper control of RA and utilization of their sequential clinical and laboratory data for clinical investigations as described in detail previously [ 15 17 ]. In the current study, we enrolled all the patients consecutively from 1st May to 31st December, 2015.…”
Section: Methodsmentioning
confidence: 99%
“…A total of 563 RA patients were enrolled from the KURAMA (Kyoto University Rheumatoid Arthritis Management Alliance) cohort and followed up prospectively. The KURAMA cohort was established in 2011 at the Center for Rheumatic Diseases in Kyoto University Hospital for tight/proper control of RA and utilization of their sequential clinical and laboratory data for clinical investigations as described in detail previously [ 15 17 ]. In the current study, we enrolled all the patients consecutively from 1st May to 31st December, 2015.…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3][4] RA could cause joint swelling, pain, loss of function and stiffness and tremendously impact on health and quality of life of patients. [5][6][7][8] The prevalence of RA is about 3 times higher in females than males.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies pointed out that mechanical stress such as excessive load causes trauma of the affected joints and therefore may significantly accelerate the initiation of inflammatory joint diseases . Yaku et al confirmed this thesis, as they demonstrated that handedness in terms of a higher mechanical demand plays a significant role for the increased incidence of RA in the dominant joints compared to the non‐dominant joints. Therefore, we assume that due to the higher exposure of the knee joint to mechanical stress, obvious signs of RA are more probable in the extremity joint than in the TMJ.…”
Section: Discussionmentioning
confidence: 91%